Conservative management of a case of a cardiac anceps twin reversed arterial perfusion sequence misdiagnosed as vanishing twin: a case report - Behura, Jharna; Sinha, Ayushi; Naaz, Aafreen; Bharti, Soni (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Twin reversed arterial perfusion (TRAP) sequence is a specific, rare and severe complication of monochorionic multiple pregnancy, which is characterized by one normal fetus (pump twin) and another with no cardiac activity and variable degree of deficient development of the head and upper limbs. The management of these pregnancies are a real challenge due to the parasitic hemodynamic dependence of the acardiac twin on the pump twin. The aim of management is to maximize the chances of survival of the pump twin with some intervention. The preferred management suggested is elective ultrasound-guided laser coagulation or radiofrequency ablation of the umbilical cord vessels at 11-13 weeks when the survival is 70-75%. Delay in intervention until 16-18 weeks is associated with spontaneous cessation of blood flow in the acardiac twin in 60% of cases and in about 50% of these there is death or brain damage in the pump twin. However, pregnancies diagnosed late need to follow a tailored approach with expectant management. The authors report a case of TRAP twin sequence which on ultrasound was diagnosed as a case of vanishing twin at 20 weeks. Subsequently on follow up ultrasound, it was diagnosed as a trap sequence with the pump twin developing polyhydramnios at 30 weeks. She was counselled regarding the prognosis of the pump twin and she opted for conservative management. Weekly ultrasound and color doppler were done. The amniotic fluid index (AFI) decreased gradually at 33 and 35 weeks, there were no signs of congestive cardiac failure of the pump twin on Doppler studies and she had a spontaneous delivery of a healthy male child and an acardiac anceps fetus at 36weeks and 5 days. The perinatal mortality of a pump twin managed conservatively ranges from 35 to 55%. It is essential to diagnose the presence of trap sequence at an early gestational age through improved imaging techniques to plan a timely and effective intervention to salvage most of the pump twins.